Prospecting in Western Ghats of Karnataka for indigenous Bacillus thuringiensis isolates harbouring novel crystal toxin genes for sugarcane pest management - Singaravelu, B; Suresha, G.S; Srikanth, J; Appunu, C; Sankaranarayanan, C; Mahesh, P; Nirmala, R; Rajeshkumar, M (Journal of Sugarcane Research, 2021)
Prospecting for potential novel Bacillus thuringiensis with new holotype crystal toxins was carried out in the Western ghats hill range of Karnataka state, India. From the soil samples collected three Bt isolates SBIKWG 12, SBIKWG 24 and SBIKWG 70 were isolated. Of these while the two isolates, namely SBIKWG 12 and SBIKWG 24 produced bipyramidal crystal toxins, the third isolate produced spherical crystal. PCR screening of the isolates revealed the presence of lepidopteran and coleopteran active cry genes. Partial sequences obtained from these isolates revealed the presence of multiple crystal toxin genes. BlastX analysis of the partial gene sequences indicated the potential for the occurrence of new holotype crystal toxin genes in SBIKWG 24 and SBIKWG 70.